Sinais digitais de um durômetro portátil para a estimativa de propriedades de madeiras para dormentes - Alexandre, Rogério Pinto [UNESP] (2015)
Currently, visual inspection has been the only control procedure by Brazilian railway concessionaires to sleepers (railroad crossties) classification, which does not guarantee, altogether, the suitability of the product specifications and has implications for the security of permanent ways. The Research Group Forest Products: Technologies and use FCA / UNESP - Botucatu, developed the third version of a portable device to evaluate the hardness of wood - Portable Hardness Tester for wood - DPM3. The device uses a displacement transducer and the acquisition of the digital signals displacement promoted during the indentation (penetration) is automated. With full monitoring of the indentation phenomenon, through the acquisition and processing of the original displacement signals, and its derivatives signs of velocity and acceleration - with use of Matlab© software, seeks to obtain prediction models of strength and stiffness properties of these woods, from characteristic parameters of these signals. To carry out the experimental program were used prismatic sleepers segments of five species of eucalyptus (E. grandis, E. viminalis, E. saligna, E. tereticornis and C. citriodora) and for each species were sampled 6 segments. The tests consisted of laboratory reference testing (compression parallel and perpendicular to the grain, bending and Janka hardness), following ABNT standards and dynamic hardness tests using DPM3. The analysis was initiated with the establishment of regression correlations between the dynamic hardness - measured by the equipment - and the ...